Objection to a decision of the court referendary in the system of legal remedies in Polish criminal proceedings - Kochel, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The article presents issues of the newly introduced legal remedy, which was introduced together with a new participant of the criminal process i.e. a court referendary under the act of 23 November 2013. To present more thoroughly the specificity of the discussed institution and to lead to further deliberations, a political position of the court referendary has been briefly described against the Polish law as well as activities entrusted to them in criminal proceedings. The procedurę of lodging and considering the objection has been analysed pointing at possible interpretative problems associated with it. Moreover, the deliberations concerning the legal nature of the objection to an activity of this judicial officer in criminal proceedings have been conducted as well as placing the regulations on submission of an objection in the criminal procedure act. Concluding de legeferenda analysis of the possibility to collect the regulations concerning the objection in one part of the code, and then to place them in the Code of Penal Procedure in case of the next amendment.